Left superior vena cava or left vertical vein in supracardiac total anomalous pulmonary venous drainage - Does it make a difference? - Radhika Uppal; Nikunj R Shekhada; Sairam Palaparthi; Suman Vyas; Byalal Raghavendrarao Jagannath (Wolters Kluwer Medknow Publications, 2022)
What do we call a vascular structure that is in the left pneumopericardial space, drains systemic venous blood, and the total pulmonary venous return, into the right atrium, through a dilated coronary sinus (CS)? Can we preserve the CS drainage while correcting the total anomalous pulmonary venous connection?